Ethical Issues in Deep Brain Stimulation Research for Treatment-Resistant Depression: Focus on Risk and Consent - Dunn, Laura B. (AJOB Neurosci, 2011)
Deep brain stimulation (DBS) is currently in pivotal trials as an intervention for treatment-resistant depression (TRD). Although offering hope for TRD, DBS also provokes ethical concerns—particularly about decision-making capacity of people with depression—among bioethicists, investigators, institutional review boards, and the public. Here, we examine this critical issue of informed consent for DBS research using available evidence regarding decision-making capacity and depression. Further, we explore the implications of the nature of TRD as well as that of the intervention (invasive brain surgery) for informed consent. Based on these analyses, we argue that additional safeguards specific to DBS research for TRD, beyond those that might be used in any higher risk study, are not supported by available empirical evidence. We nevertheless underscore the limited data on such invasive procedures in severely ill psychiatric patients and advocate a research agenda for the systematic study of ethical issues raised by these research endeavors.